The Effectiveness of Using Picture Series Media on Students’ Writing Skills in Narrative Text at SMP St. Petrus Medan - Desvinna Sinuhaji; Fiber Yun Almanda Ginting; Jenita Anjani Sembiring (Universitas Majalengka, 2026)
Writing is one of the essential language skills that enables students to communicate ideas effectively in written form. However, many junior high school students continue to experience difficulties in developing narrative texts due to limited vocabulary, poor organization of ideas, and lack of creativity in expressing story events. Although Picture Series Media has been widely implemented in English language teaching, limited studies have specifically examined its effectiveness in improving narrative writing skills among ninth-grade students using a quasi-experimental design in Indonesian junior high schools. Therefore, this study aimed to investigate the effectiveness of Picture Series Media on students’ writing skills in narrative texts at SMP St. Petrus Medan. A quantitative approach employing a quasi-experimental design was applied. The population consisted of 127 ninth-grade students, from which 62 students were selected through purposive sampling and assigned to an experimental group and a control group, each consisting of 31 students. Data were collected through pre-test and post-test writing assessments and analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, Paired Samples t-test, and Independent Samples t-test using IBM SPSS Statistics. The findings revealed that the experimental group achieved a substantially higher post-test mean score (80.61) than the control group (72.68). Statistical analysis indicated a significant improvement in students’ writing achievement (p < .001). These findings demonstrate that Picture Series Media effectively improves students’ narrative writing skills by facilitating idea generation, organizing story sequences, and encouraging students’ creativity in writing activities. Therefore, Picture Series Media can be considered an effective instructional medium for teaching narrative writing in EFL classrooms.